Observation of photoconductivity in Sn-doped ZnO nanowires and their photoenhanced field emission behavior - Sheini, Farid Jamali; More, Mahendra A.; Jadkar, Sandesh R.; Patil, K. R.; Pillai, Vijaymohanan K.; Joag, Dilip S. (Journal of Physical Chemistry C, 2010)
Sn-doped ZnO nanowire films have been Successfully synthesized by electrodeposition oil zinc foil followed by annealing in air at 400 degrees C for 4 h. The XRD patterns of the annealed specimens exhibit I set of well-defined diffraction peaks indexed to the wurtzite phase of ZnO. The Surface morphology of the as-synthesized films showed a network of densely packed flakes/sheets oil the Substrate. However, upon annealing, the formation of ZnO nanowires, processing length in the range of several micrometers and diameter less than 150 nm, oil the entire substrate is observed. The relative atomic percentage of Sri, estimated from the energy dispersive spectra, was found to be 0.5 and 2.0 in the ZnO films deposited for 10 and 40 min durations, respectively. Front the field emission studies, the Values of the turn-on field and threshold field, required to draw emission Current density of 10 and 100 mu A/cm(2), are observed to be 0.68 and 1.1 V/mu m for 0.5% Sn-doped ZnO and 1.72 and 2.25 V/mu m for 2.0% Sn-doped ZnO, respectively. The field emission Current stability investigated for a duration Of h at the preset value of 100 mu A is found to be excellent. A prominent photoenhancement in the field emission Current upon visible light illumination of the Sn-doped ZnO nanowires films has been observed. This enhancement has been attributed to the photoconductivity of the Sn-doped ZnO.

Optical antenna effect on SiNWs/CuS photodiodes - Yenchalwar, Sandeep G.; Rondiya, Sachin R.; Shinde, Pravin N.; Jadkar, Sandesh R.; Shelke, M. V. (Physica Status Solidi A-Applications and Materials Science, 2017)
One-dimensional architectures between silicon nanowires (SiNWs) and CuS were fabricated by radio-frequency (RF) magnetron sputtering and analyzed for solid-state photodetector application. Inspired by the subwavelength optical concentration by the surface plasmons on metal nanostructures at the nanoscale, we investigated the effect of gold nanorods (AuNRs) on the optical absorption and photodetection properties of the heterojunction photodiode. AuNRs acting as an optical trapping antenna enhances the light absorption, consequently boosting the photocurrent from the device. A maximum photoresponsivity of 0.36 mA W-1 was achieved under 665 nm excitation wavelength independent of the bias, a value similar to 13 times higher than for the heterojunction photodiode without AuNRs. Such plasmonic sensitization can be useful for improving the sensitivity of visible as well as IR photodetectors. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim